Improved survival and complete response rates in patients with advanced melanoma treated with concurrent ipilimumab and radiotherapy versus ipilimumab alone. Issue 1 (2nd January 2017) - Koller, Kristian M.; Mackley, Heath B.; Liu, Jason; Wagner, Henry; Talamo, Giampaolo; Schell, Todd D.; Pameijer, Colette; Neves, Rogerio I.; Anderson, Bryan; Kokolus, Kathleen M.; Mallon, Carol A.; Drabick, Joseph J.
ABSTRACT: There is a growing body of evidence supporting the synergistic roles of radiotherapy and immunotherapy in the treatment of malignancy. Published case studies of the abscopal effect have been reported with the use of ipilimumab and radiotherapy in metastatic melanoma, but evidence supporting the routine use of this combination of therapy is limited. We conducted a retrospective analysis to evaluate patients treated with ipilimumab for advanced melanoma at a single institution from May 2011 to June 2015. Patients were grouped into those who had received concurrent radiotherapy while on ipilimumab (Ipi-RT), and those who did not. We then evaluated the treatment response following completion of ipilimumab. A total of 101 patients received ipilimumab in the prespecified time frame. 70 received Ipi-RT and 31 received ipilimumab without concurrent radiotherapy. Median overall survival (OS) was significantly increased in the concurrent Ipi-RT arm at 19 months vs. 10 months for ipilimumab alone (p = 0.01). Median progression free survival (PFS) was marginally increased in the Ipi-RT group compare with the ipilimumab alone group (5 months vs. 3 months, p = 0.20). Rates of complete response (CR) were significantly increased in the Ipi-RT group vs. ipilimumab alone (25.7% vs. 6.5%; p = 0.04), and rates of overall response (OR) in the groups were 37.1% vs. 19.4% (p = 0.11). No increase in toxicities was observed in the Ipi-RT group compare with ipilimumab alone. Prospective trials are needed to further clarify the role of radiotherapy with ipilimumab, but these encouraging preliminary observations suggest that this combination can induce more durable responses to immunotherapy.